Central Asia's comparative advantage in international trade - Matthias Lücke; Jacek Rothert (Kiel Institute for the World Economy (IfW), 2006)
This paper outlines a strategy for identifying the pattern of Central Asia's comparative advantage in international trade, based on factor prices and transport costs, historical production patterns, and recent trends in the geographical and product composition of Central Asian trade. The paper focuses on Kazakhstan, the Kyrgyz Republic, Tajikistan, and Uzbekistan, along with Azerbaijan and Mongolia. A country's comparative advantage cannot be determined at the level of individual industries or products. At the same time, policymakers benefit from an awareness of a country's general pattern of comparative advantage as they prioritize measures for promoting nontraditional exports or policy reforms to reduce barriers to trade, whether related to trade policy instruments, to transport and transit, or to the investment climate. A comparison of manufacturing wages in the region with key competitors shows that the resource rich countries (Kazakhstan and Azerbaijan) with monthly wages above 100 will hardly be able to compete on price in labor-intensive exports to the world market (e.g., in direct competition with China). For the remaining countries with lower wages, the viability of particular labor-intensive exports would have to be assessed from detailed estimates of cost structures, including buildings and transport. As they are geographically remote, it is very difficult for Central Asian countries to expand exports by integrating into production networks operated by European firms (a strategy employed with much success in Central and Eastern Europe). Enhanced processing of local raw materials that are already exported (such as cotton) will often be a more viable option. At present, Central Asia's exports are dominated by unprocessed or semi processed commodities. Prominent export products vary somewhat across countries, so that export growth would not push Central Asian countries to compete in all the same products. Many trade flows are also so small in relation to potential markets (Russia, Western Europe, etc.) that ruinous export competition is unlikely. For several industrial products, Central Asian countries are significant exporters to CIS countries, but not to the rest of the world. Such products could be focal points for export diversification into nontraditional markets.
Keywords: 330; Komparativer Kostenvorteil; Internationaler Wettbewerb; Außenhandelsstruktur; Zentralasien; Kasachstan; Kirgisistan; Tadschikistan; Usbekistan; Aserbaidschan; Mongolei